Age-specific associations between environmental factors and epistaxis - Ahn, Eun-Jin; Min, Hyun Jin (Frontiers in Public Health, 2022)
Objective Several studies have demonstrated that environmental factors, such as meteorological factors and air pollutants, are closely associated with epistaxis. However, age-specific associations between environmental factors and epistaxis have not yet been evaluated. This study aimed to evaluate the associations between individual meteorological factors and air pollutants and epistaxis, by age. Study design A retrospective cohort study. Setting Records of patients covered by the Korean National Health Insurance Service who visited our hospital for epistaxis between January 1, 2002, and December 31, 2015, were retrospectively reviewed. Methods The 46,628 enrolled patients were divided into four age groups: age group 0 (<18 years, N = 19,580); age group 1 (18–40 years, N = 10,978); age group 2 (41–70 years, N = 13,395); and age group 3 (>70 years, N = 2,675). Cases of epistaxis and data on environmental factors were analyzed according to the day, month, and year. Stepwise logistic regression was performed to identify the environmental risk factors for epistaxis in each age group. Results Age group 0 had the highest number of patients with epistaxis, whereas age group 3 had the lowest. Relative humidity, temperature, concentrations of particulate matter (PM10) and sulfur dioxide, sunshine duration, and wind speed were significantly associated with the occurrence of epistaxis in the study population. However, analysis according to age group showed that the meteorological factors and air pollutants associated with epistaxis were different in each age group. Conclusion We suggest that the environmental risk factors for epistaxis should be differentially analyzed according to age.